196 High-Resolution Magnetic Resonance Imaging in Trigeminal Neuralgia: Added Benefit of Contrast Enhanced Constructive Interference in Steady State Imaging. (August 2016) - Goodwin, C. Rory; Seeburg, Daniel; Northcutt, Benjamin; Shin, Jaehoon; Theodros, Debebe; Abu-Bonsrah, Nancy A.; Herzka, Daniel; Aygun, Nafi; Blitz, Ari M; Lim, Michael
Abstract : INTRODUCTION: MRI is performed in the assessment of patients with trigeminal neuralgia (TGN). However, there is poor contrast between vessels and nerves, because both are low in intensity on heavily T2-weighted images. METHODS: A retrospective review was performed of high-resolution 3D MRI studies of patients from 2011 to 2014. Eighty-one TGN patients and 15 controls were independently reviewed by 2 neuroradiologists in a blinded fashion. The cisternal segment of the trigeminal nerve root was assessed bilaterally for metrics of neurovascular conflict, including grade (0-3), nerve root cross-sectional area (CSA), and degree of flattening (DOF). The data were correlated with side of symptoms and postoperative pain relief after microvascular decompression (MVD). RESULTS: Grade 1 neurovascular conflict was prevalent on both the asymptomatic side (59.3%) and in controls (60%), but advanced grade neurovascular conflict was rare on the asymptomatic side (7.4%) and not seen in controls (0%). Grade 3 neurovascular conflict occurred in 46.9% on the symptomatic side, but was highly specific for that side (94.6%). Review of contrast-enhanced 3D constructive interference in steady state (CISS) imaging (CE-CISS) more than doubled the prevalence of grade 3 neurovascular conflict (14.8% vs 33.3%, P = .001), and yielded lower CSA and greater DOF for advanced grade neurovascular conflict on the side of symptoms compared with imaging without contrast (NE-CISS). Patients with complete pain relief after MVD had significantly lower CSA on CE-CISS compared with NE-CISS on preoperative imaging. The area under the curve (AUC) for predicting complete relief of symptoms after MVD was significantly higher for CE-CISS than for NE-CISS for grade of neurovascular conflict (AUC = 0.835 vs 0.803, P = .017) and CSA (AUC = 0.709 vs 0.682, P = .002). CONCLUSION: The addition of gadolinium-based contrast to 3D-CISS imaging improves performance in predicting the side of symptoms in patients with TGN and in predicting favorable outcomes after MVD, which may be helpful in preoperative planning.